Gallic‐Acid‐Modified Naphthalimide Containing Disulfide Bond as Reduction‐Responsive Supramolecular Organogelator. Issue 17 (3rd May 2022) - Pei, Qiang; Han, Qingqing; Tang, Fang; Wu, Jinjin; Xu, Shijie; Zhang, Mengyao; Ding, Aixiang
Abstract: The development of low molecular‐weight gelators for the construction of stimuli‐responsive gels is increasing attention because of the great application potential. In this work, we report the design and synthesis of two new naphthalimide derivatives,  GSSN  and GN, as supramolecular organogelators. GSSN  contains a disulfide bond in the molecule, while GN  contains no disulfide bond. As a result, only GSSN  exhibited reduction responsiveness. A series of tests, including UV‐vis, temperature‐dependent 1 H NMR, XRD, and SEM, were carried out to characterize the gelation capability and probe into the gelation mechanism. Results showed that GN  can gelate more organic solvents than GSSN . Both hydrogen bonding and π stacking contribute to the gelation. Due to the difference in the assembly of the organogelator molecules, the organogels formed by GSSN  and GN  presented distinct morphologies. Moreover, strong hydrophobicity was found in the organogel films of GSSN  and GN, suggesting potential application as hydrophobic coating materials. Abstract : Two new naphthalimide derivatives,  GN  and GSSN, have been synthesized as low‐weight molecular organogelators. Both compounds can gelate organic solvents at low concentrations. A series of characterizations reveal that the gelation is attributed to the synergistic effect of multiple supramolecular interactions, including hydrogen bonding, van der Waals interaction, and π stacking. Particularly, redox‐responsiveness was demonstrated in the GSSN  organogel due to the incorporation of a disulfide bond into the molecule.